An Analysis of Inclusiveness in Teaching Citizenship Education (Civic Education) in Primary Schools: A Case Study of Curriculum Implementation and Inclusive Practices - Retnasari, Lisa; Putri, Ragil Dian Purnama; Wardani, Ella Kusuma; Abdulkarim, Aim; Baehaqi, Dikdik (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
This research aims to analyze inclusivity in the teaching of Civic Education (PKn) in elementary schools, with a focus on the implementation of inclusive curriculum and practices. This research uses a case study approach to understand inclusivity in the context of Citizenship Education in elementary schools. The aim of this research is to analyze inclusivity in Civics teaching in elementary schools through case studies of the implementation of inclusive curriculum and practices and understand the extent to which inclusivity is implemented in the Civics teaching curriculum and practices in elementary schools. This research is a case study research with a qualitative approach to gain an in-depth understanding of inclusivity in Civics teaching in elementary schools. This approach will allow researchers to explore the perceptions, experiences, and practices in a more holistic context. Data collection uses observation, interviews, and documentation. The research subjects were principals, teachers, and students at SDN Pakel, SDN Wirosaban and SDN Giwangan. The data analysis technique uses data triangulation. The results of this research reveal variations in the implementation of Civics inclusiveness in elementary schools. Factors such as teacher understanding, available resources, and school support play an important role in achieving inclusivity. SDN Giwangan shows a strong commitment to inclusivity by providing additional support for students who need it, while SDN Pakel and SDN Wirosaban still face obstacles in creating a truly inclusive learning environment. This research provides insight into the challenges and opportunities in realizing inclusivity in citizenship education and provides a basis for further improvements in efforts to create a more inclusive learning environment for all students.